2020
DOI: 10.21776/ub.jitek.2020.015.01.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Skim Milk Concentration on Sensory Quality and pH of Probiotic Yoghurt Added with Red Dragon Fruit (Hylocereus polyrhizus)

Abstract: Probiotic yoghurt is one of dairy products that has benefits to the human health. This research aimed to understand the effect of skim milk concentration on the sensory quality traits and pH of probiotic yoghurt added with red dragon fruit (Hylocereus polyrhizus) dices prior to the fermentation. The research method was experimental method with 4 treatments and 3 replications in a completely randomized group design. The data were analyzed using one-way analysis of variance followed by Duncan's multiple range te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…We concluded that using skim milk will have better consistency and sensory characteristics that the other two. In line with our trials, several studies mentioned the advantages of using skim milk including lower price and a positive relation with probiotic viability and fermented milk flavor [31][32][33].…”
Section: Production Of Synbiotic Fermented Milk With Double Fortificasupporting
confidence: 87%
“…We concluded that using skim milk will have better consistency and sensory characteristics that the other two. In line with our trials, several studies mentioned the advantages of using skim milk including lower price and a positive relation with probiotic viability and fermented milk flavor [31][32][33].…”
Section: Production Of Synbiotic Fermented Milk With Double Fortificasupporting
confidence: 87%
“…Fermentation process and skim milk concentration may affect rheology properties of probiotic drink. Texture of the probiotic drink may be affected by dissolved protein denatured thus forming semi solid texture and increasing product viscosity [32]. Effect of starter type and skim milk concentrations can be seen in Table 4.…”
Section: Protein and Viscositymentioning
confidence: 99%
“…It was also clear that viscosity of whey probiotic drink increased along with higher concentrations of skim milk. Hafizha et al [32] reported that elevated concentrations of skim milk may increase viscosity of probiotic yoghurt. High viscosity shows thicker probiotic drink [33].…”
Section: Protein and Viscositymentioning
confidence: 99%